PENGARUH PERTUMBUHAN EKUITAS DAN PERTUMBUHAN LABA TERHADAP INVESTMENT OPPORTUNITY SET - Karsam, Karsam; Yanalia Salampessy, Yanalia Salampessy (Jurnal Riset Akuntansi dan Keuangan, 2013)
This study uses a sample of 35 companies engaged in the Property and Real Estate Industries listed on the Indonesia Stock Exchange (IDX) period 2004-2008. Data source is secondary data obtained from Indonesian Capital Market Directory with data collection is done by time series.The results of the analysis show that simultaneously Growth Equity and Profit Growth affect Investment Opportunity Set especially on Market Book Value of Asset (MBVA) ratio. While partially, Growth Equity and Profit Growth significantly influence Investment Opportunity Set especially in Market Book Value of Asset (MBVA) raidtio.